The DprE1 Inhibitors: Enduring aspirations for future Anti-TB Drug Discovery - Yadav Saloni; Soni Aastha; Tanwar Omprakash; Bhadane Rajendra; Besra Gurdyal S.; Kawathekar Neha (Wiley-VCH GmbH, 2025)
DprE1 is a crucial enzyme involved in the cell wall synthesis of Mycobacterium tuberculosis and a promising target for anti-TB drug development. However, its unique structural characteristics for ligand binding and association with DprE2 make developing new clinical compounds challenging. This review provides an in-depth analysis of the structural requirements for both covalent and non-covalent inhibitors, their 2D and 3D binding patterns, as well as their biological activity data in vitro and in vivo, including pharmacokinetic information. We also introduce a protein quality score (PQS) and an active-site map of the DprE1 enzyme to help medicinal chemists better understand DprE1 inhibition and develop new, effective anti-TB drugs. Furthermore, we examine the resistance mechanisms associated with DprE1 inhibitors to understand future developments due to resistance emergence. This comprehensive review offers insights into the DprE1 active site, including protein-binding maps, PQS, and graphical representations of known inhibitors, making it a valuable resource for medicinal chemists working on future antitubercular compounds